Effects of fluorine substitution on substrate conversion by cytochromes P450 17A1 and 21A2. Issue 35 (25th August 2021) - Vogt, Caleb D.; Bart, Aaron G.; Yadav, Rahul; Scott, Emily E.; Aubé, Jeffrey
Abstract : Cytochromes P450 17A1 (CYP7A1) and 21A2 (CYP21A2) catalyze key reactions in the production of steroid hormones, including mineralocorticoids, glucocorticoids, and androgens. Abstract : Cytochromes P450 17A1 (CYP7A1) and 21A2 (CYP21A2) catalyze key reactions in the production of steroid hormones, including mineralocorticoids, glucocorticoids, and androgens. With the ultimate goal of designing probes that are selectively metabolized to each of these steroid types, fluorinated derivatives of the endogenous substrates, pregnenolone and progesterone, were prepared to study the effects on CYP17A1 and CYP21A2 activity. In the functional assays, the hydroxylase reactions catalysed by each of these enzymes were blocked when fluorine was introduced at the site of metabolism (positions 17 and 21 of the steroid core, respectively). CYP17A1, furthermore, performed the 17, 20-lyase reaction on substrates with a fluorine installed at the 21-position. Importantly, none of the substitutions examined herein prevented compound entry into the active sites of either CYP17A1 or CYP21A2 as demonstrated by spectral binding assays. Taken together, the results suggest that fluorine might be used to redirect the metabolic pathways of pregnenolone and progesterone to specific types of steroids.